The contribution of the accounting investigation to the regular collection revenues - The Directorate of Major Institutions as a model - - habbar, mohamedamine; nacer, mourad (Journal of Research in Finance and Accounting, 2022)
This study reveals how does the accounting investigation, as an important means of fiscal control, contribute to increasing the regular collection revenues, with the aim of monitoring its repercussions on tax collection and raising its revenues. Through a field study of the "Directorate of Major Institutions in Algiers", and the use of description and analysis in reading the statistics of the institution’s accounting investigation results between (2017-2020), the study concluded that the accounting investigation is an effective way to increase the revenues of ordinary collection, and although the period of accounting investigation of files is four years, not obsolete, this does not conflict with the role played by this type of control in correcting accounting errors and thus remedying the taxes and fees omitted by the taxpayer.